Comparative profiling of surgically resected primary tumors and their lymph node metastases in small-cell lung cancer - Csende, K; Ferencz, B; Boettiger, K; Pozonec, M D; Lantos, A; Ferenczy, A; Pipek, O; Solta, A; Ernhofer, B; Laszlo, V; Megyesfalvi, E; Schelch, K; et al. (ESMO open, 2025)
BACKGROUND: Profiling studies in small-cell lung cancer (SCLC) have mainly focused on primary tumors, omitting the potential molecular changes that might occur during lymphatic metastasis formation. Here, we assessed the molecular discordance between primary SCLCs and corresponding lymph node (LN) metastases in the light of subtype distribution and expression of clinically relevant proteins. METHODS: Comparative profiling of 32 surgically resected primary SCLCs and their LN metastases was achieved by RNA expression analysis and immunohistochemistry (IHC). In addition to subtype markers (ASCL1, NEUROD1, POU2F3, and YAP1), the expression of nine cancer-specific proteins was evaluated. RESULTS: The selected clinically relevant molecules showed no significant differences in their RNA expression profile when assessing the primary tumors and their corresponding LN metastases. Nevertheless, IHC analyses revealed significantly higher DLL3 expression in the primary tumors than in the LN metastases (P = 0.008). In contrast, NEUROD1 expression was significantly lower in the primary tumors (versus LN metastases, P < 0.001). No statistically significant difference was found by IHC analysis in the case of other clinically relevant proteins. Concerning SCLC molecular subtypes, a change in subtype distribution was detected in 21 cases. Phenotype switching from neuroendocrine (NE) subtypes toward non-NE lesions and from non-NE landscape toward NE subtypes were both detected. CONCLUSIONS: Although the molecular landscape of SCLC LN metastases largely resembles that of the tumor of origin, key differences exist in terms of DLL3 and NEUROD1 expression, and in subtype distribution. These diagnostic pitfalls should be considered when establishing the tumors' molecular profile for future clinical trials solely based on LN biopsies.
Keywords: transkripční faktory bHLH; Small Cell Lung Carcinoma; Male; nádory plic; Lung Neoplasms; Basic Helix-Loop-Helix Transcription Factors; metastasis; Aged; imunohistochemie; mužské pohlaví; senioři; malobuněčný karcinom plic; Lymphatic Metastasis; intertumoral heterogeneity; lidé; ženské pohlaví; Immunohistochemistry; Biomarkers, Tumor; Humans; small-cell lung cancer; subtypes; lymfatické metastázy; Female; lidé středního věku; nádorové biomarkery; Middle Aged